Systematic Literature Review: Efektivitas Ekstrak Kopi sebagai Antioksidan dalam Mengatasi Photoaging - Ratri, Oktavia Lestyaning; Ebtavanny, Tamara Gusti; Puspita, Oktavia Eka (Pharmaceutical Journal of Indonesia, 2021)
Aging of the skin due to exposure of UV rays is referred as photoaging.  Photoaging causes dry skin, wrinkles, darker skin pigmentation, and reduced skin firmness. The effect of photoaging can be treated by compounds that have antioxidant activity. Coffee contains polyphenols (caffeic acid and chlorogenic acid) which can inhibit the formation of ROS free radicals. This makes coffee an antioxidant potential in photoaging treatment. This study aims to determine the effectiveness of coffee extract as an antioxidant in photoaging treatment. The method used in this study is Systematic Literature Review. A comprehensive literature search was conducted using the Harzing's Publish or Perish application on several databases, such as Google Scholar, PubMed, Scopus, and Crossref using the keywords "coffee AND antioxidant AND ultraviolet AND photoaging". The article selection flow used the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) protocol. The total search results were 1202 articles, and there were 6 research articles that matched the inclusion and exclusion criteria that had been set. The results of this study concluded that coffee extract can be used as an antioxidant in photoaging treatment. The effectiveness of coffee extract as an antioxidant in photoaging treatment was demonstrated by reducing the expression of MMPs, increasing the expression of type 1 procollage, reducing the area of wrinkles, and reducing TEWL. Coffee leaf extract decreased the expression of MMPs (MMP-1 ¯ 50%, MMP-3 ¯ 10% to 60%, MMP-9 ¯ 30% to 50%) and increased type 1 procollagen 60%. Coffee bean extract decreased the expression of MMPs (MMP-1 ¯ 5% to 60%, MMP-2 ¯ 20% to 60%, MMP-3 ¯  30%, MMP-9 ¯ 20% to 70%, MMP-13 ¯ 30% to 45%), increased type 1 procollagen 10% to 60%, reduced wrinkle area 20% to 88%, and decreased TEWL 10% to 20%.